Impact of hysterosalpingography on endometrial HOXA-10 and HOXA-11 mRNA expression: A clinical trial - Ozdemir, Fatma; Demir, Mustafa Bertan; Kutuk, Serhan; Karaman, Enes; Muderris, Iptisam Ipek; Celik, Onder; Dalkilic, Lutfiye Kadioglu (Lippincott Williams & Wilkins, 2025)
Background: Homeobox genes (HOX) are the basic molecules that regulate endometrial receptivity, decidualization, and progesterone response. This study was designed to investigate the effects of the classical hysterosalpingography (HSG) procedure on endometrial HOXA-10 and 11 mRNA expression. Methods: Thirty-five primary infertile patients who applied for investigation of infertility etiology and were approved for conventional HSG were included in the study. Ten fertile patients who required biopsy due to an endometrial pathology were accepted as a control group. Women in HSG group were eligible to participate in the study if they were between 22 and 34 years of age, had spontaneous menstrual cycles, and had been trying to conceive for at least 1.5 year and if there was an indication for evaluation of tubal patency with hysterosalpingography. First endometrial sampling was performed with a pipelle before the contrast-medium infusion during the HSG. Endometrial sampling was collected for the second time with a pipelle cannula in the midluteal phase of the next cycle in all cases undergoing HSG. HOXA-10 and 11 mRNA expressions in the endometrial tissues obtained before HSG and respective endometrial tissues after HSG were measured with RT-PCR. Results: Pre-HSG average Delta Ct values of HOXA-10 and HOXA-11 mRNA were found to be significantly lower than fertile controls (4.30 vs 6.74, P < .001; 3.93 vs 6.74, P < .002). Post-HSG HOXA-10 mRNA levels increased significantly compared to pre-HSG levels (5.66 vs 4.30, P < .01). Post-HSG HOXA-10 mRNA levels increased approximately 4.2-fold compared to pre-HSG levels. Post-HSG HOXA-11 mRNA levels increased significantly compared to pre-HSG levels (4.94 vs 3.93, P < .03). Post-HSG HOXA-11 mRNA levels increased approximately 3.5-fold compared to pre-HSG levels. When the pre-HSG and post-HSG HOXA-10 and HOXA-11 mRNA levels were compared among themselves, the increase in HOXA-10 average Delta Ct was significantly higher than the increase in HOXA-11 average Delta Ct (5.66 vs 4.94, P < .02.). Similarly, the fold increase in post-HSG mRNA levels was significantly higher in the HOXA-10 group (4.2-fold) than the HOXA-11 group (3.5-fold) (P < .001). Conclusions: Conventional HSG procedure improves fertility by increasing endometrial HOXA-10 and HOXA-11 mRNA levels.
Keywords: endometrium; HOXA-10 mRNA; HOXA-11 mRNA; HSG; receptivity; RT-PCR